Unionization, stochastic dominance, and compression of the wage distribution: Evidence from Germany - Michael C. Burda; Bernd Fitzenberger; Alexander C. Lembcke; Thorsten Vogel (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
This paper establishes theoretical and empirical linkages between union wage setting and the structure of the wage distribution. Theoretically, we identify conditions under which a right-to-manage model implies compression of the wage distribution in the union sector relative to the nonunion sector as well as first-order stochastic dominance. These implications are investigated using quantile regressions on the 2001 GSES, a large German linked employeremployee data set which contains explicit information on coverage by collective agreements. The empirical results confirm that, in case of industry-wide collective agreements, log union wage effects decline in quantiles, implying union wage compression. This finding, however, cannot be corroborated for wages determined at the firm level. Stochastic dominance is confirmed, as predicted by the theoretical model, for both types of collective agreements.
Keywords: J31; J51; J52; 330; Union wage effect; stochastic dominance; wage compression; quantile regressions; Machado-Mata decomposition; Lohnstruktur; Lohnbildung; Lohnpolitik; Gewerkschaftlicher Organisationsgrad; Schätzung; Deutschland